Protection of GnRH analogue by chitosan-dextran sulfate nanoparticles for intravaginal application in rabbit artificial insemination - Casares-Crespo, Lucía; Fernández-Serrano, Paula; Viudes-De-Castro, María P. (2019)
The present study was designed to prove new rabbit insemination extenders containing aminopeptidase inhibitors (AMIs) with or without chitosan (CS)-dextran sulfate (DS) nanoparticles entrapping the GnRH analogue. In addition, different hormone concentrations were tested in these extenders, evaluating their in vivo effect on rabbit reproductive performance after artificial insemination. A total of 911 females were inseminated with semen diluted with the four experimental extenders (C4 group: 41 mu g buserelin/doe in control medium (Tris-citric acid-glucose supplemented with bestatin 10 mu M and EDTA 20 mM), C5 group: 5 mu g of buserelin/doe in control medium, Q4 group: 414 of buserelin/doe into CS-DS nanoparticles in control medium, Q5 group: 5 mu g of busereline/doe into CS-DS nanoparticles in control medium). Results showed that fertility was significantly lower in C4 group compared to C5, Q5 and Q4 groups (0.7 versus 0.85, 0.85 and 0.82, respectively). On the contrary, prolificacy was similar in the four experimental groups studied (P> 0.05). We conclude that the CS-DS nanoparticles prepared by a coacervation process as carrier for buserelin acetate allows reducing the concentration of hormone used in extenders supplemented with bestatin and EDTA without affecting the fertility and prolificacy of rabbit females. (C) 2018 Elsevier Inc. All rights reserved.